2006
DOI: 10.3748/wjg.v12.i38.6161
|View full text |Cite
|
Sign up to set email alerts
|

The timing of bowel preparation before colonoscopy determines the quality of cleansing, and is a significant factor contributing to the detection of flat lesions: A randomized study

Abstract: The quality of colonic cleansing and the detection of flat lesions are significantly improved when the preparation is taken on the day of the colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
138
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(152 citation statements)
references
References 24 publications
7
138
1
6
Order By: Relevance
“…It should be noted that PEG-EA subjects were permitted a more liberal diet, including a regular breakfast and a light lunch, before bowel cleansing in contrast to sulfate subjects who were restricted to clear liquids aft er a light breakfast. Th e infl uence of these dietary diff erences on bowel preparation quality is unknown.Th e fi ndings of Di Palma et al confi rm the results of previously published studies (3,9,10) showing that a split-dosing strategy, in which a proportion of the bowel preparation is taken on the morning of the examination, results in superior bowel cleansing compared with a regimen that provides the entire bowel preparation the day before the examination. Splitdosing should now be a practice standard for pre-colonoscopic…”
supporting
confidence: 59%
See 1 more Smart Citation
“…It should be noted that PEG-EA subjects were permitted a more liberal diet, including a regular breakfast and a light lunch, before bowel cleansing in contrast to sulfate subjects who were restricted to clear liquids aft er a light breakfast. Th e infl uence of these dietary diff erences on bowel preparation quality is unknown.Th e fi ndings of Di Palma et al confi rm the results of previously published studies (3,9,10) showing that a split-dosing strategy, in which a proportion of the bowel preparation is taken on the morning of the examination, results in superior bowel cleansing compared with a regimen that provides the entire bowel preparation the day before the examination. Splitdosing should now be a practice standard for pre-colonoscopic…”
supporting
confidence: 59%
“…Th e importance of bowel preparation before colonoscopy cannot be understated. Inadequate colon cleansing is associated with lower endoscopic yield for adenomas (1,2) , decreased fi nd rates for fl at lesions (3), and longer examinations (2) . Unfortunately, bowel preparation is oft en inadequate to permit complete examination of the colon (1) , necessitating shorter screening and surveillance intervals.…”
mentioning
confidence: 99%
“…Despite more than 14 million colonoscopies being performed each year, the historic rates for adequate cleansing are unacceptably low and range from 70-82% (10)(11)(12)(13). Recent studies have shown that ingesting at least part of the purgative on the day of colonoscopy and coordinating the final dose of purgative with the start time of colonoscopy is more likely to result in adequate colon cleansing (2)(3)(4)(5). Generally, this is accomplished by splitting the purgative between the evening prior and the morning of colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups of patients in the study presented herein were asked to complete the second dose of PEG-ELS 4 hours before their scheduled procedure time. Aspiration, though rare, is serious and has not been reported in several studies that have specifically evaluated PEG-ELS dosing on the day of colonoscopy (2)(3)(4)(5)8). Large published series of patients receiving propofol-based anesthesia for endoscopy have found aspiration to be a rare event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation